2019
DOI: 10.1002/ped4.12111
|View full text |Cite
|
Sign up to set email alerts
|

Variant analysis of the chromodomain helicase DNA‐binding protein 7 in pediatric disorders of sex development

Abstract: Importance: This study investigated the role of the chromodomain helicase DNA-binding protein 7 (CHD7) in disorders of sex development (DSD). Objective: We aimed to present the potential pathogenicity of CHD7 variants in pediatric patients with DSD. Methods: Choosing cases with CHD7 variants from DSD patients in Beijing Children's Hospital to assess for the study. Prediction software tools were used to predict variant pathogenicity in these subjects. results: Among the 113 DSD patients, 22 cases had CHD7 varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
(18 reference statements)
1
1
0
Order By: Relevance
“…KS patients are more likely to have abnormal olfactory function, but it is also common for patients with abnormal olfactory bulb to have normal olfactory function. In this study cohort, most male patients had reproductive system abnormalities with a high incidence, such as micropenis (92.3%), cryptorchidism (41.7%), penis retraction (7.7%), and scrotal division (7.7%), which were consistent with literature reports [16][17][18][19]. These findings suggest the possibility and necessity of early diagnosis of IHH.…”
Section: Molecular Genetic Analysissupporting
confidence: 89%
See 1 more Smart Citation
“…KS patients are more likely to have abnormal olfactory function, but it is also common for patients with abnormal olfactory bulb to have normal olfactory function. In this study cohort, most male patients had reproductive system abnormalities with a high incidence, such as micropenis (92.3%), cryptorchidism (41.7%), penis retraction (7.7%), and scrotal division (7.7%), which were consistent with literature reports [16][17][18][19]. These findings suggest the possibility and necessity of early diagnosis of IHH.…”
Section: Molecular Genetic Analysissupporting
confidence: 89%
“…CHD7 c.409T>G(p.S137A) in the ClinVar database was also reported to be benign or likely benign, with no specific disease description. Other studies reported c.2182G>A(p.D728N) of CHD7 in IHH or CHARGE syndrome [ 16 18 ], c.1369A>G(p.T457A) of SEMA3A [ 19 ], and c.749G>A(p.R250H) of CHD7 in abnormal sexual development [ 20 ]. At the same time, no focal duplication of ANOS1 gene has been reported, and only multiple abnormal patients with multiple gene duplication have been reported [ 21 ].…”
Section: Resultsmentioning
confidence: 99%